Dietary patterns and its associations with adipokines (adiponectin and leptin) among adults: a narrative review - Nor Syamimi Zakarai,; Mohd Razif Shahril, (Penerbit Universiti Kebangsaan Malaysia, 2017)
To compile and analyse existing scientific evidence regarding the association of dietary patterns with adiponectin and leptin. Medline and PubMed electronic databases were searched for articles related to the association of dietary patterns with adiponectin and leptin from 2005 to 2015. Only full text articles using English as a language of publication were included. Studies were limited to the use of food frequency questionnaires in assessing dietary intake, factor analysis using principal component analysis, cluster analysis or reduced rank regression method in determining dietary pattern. A total of six relevant studies involving a total of 6467 subjects (47% men and 53% women) met the inclusion criteria from 1407 reviewed articles Twelve dietary patterns were extracted i.e. healthy pattern, meat and fat, sweet pattern, potatoes and refined grains, Japanese pattern, westernized pattern, mixed pattern, traditional pattern, vegetables, fruits and lean meat pattern, high alcohol, ‘Izakaya’ pattern and dieting. Two studies showed association with leptin which serum leptin concentration showed significantly higher in vegetables, fruits and lean meat compared to western pattern and lower circulating levels of leptin in westernized breakfast dietary pattern. Adiponectin concentration resulting significant positive relationship with fruits and vegetables, dieting, Japanese and healthy dietary pattern. Adherence to healthy dietary patterns plays an important role on serum adiponectin and leptin concentration. However, in most studies that resulted in a significant relationship, adiponectin, leptin and diet components were evaluated separately. Therefore, further well-designed studies were required to clarify the mechanism mediating relationship between dietary patterns and adipokines.